2021
DOI: 10.1289/ehp9044
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Low-Level NO2 and Mortality among the Elderly Population in the Southeastern United States

Abstract: Background: Mounting evidence has shown that long-term exposure to fine particulate matter [PM in aerodynamic diameter ( )] and ozone ( ) can increase mortality. However, the health effects associated with long-term exposure to nitrogen dioxide ( ) are less clear, in particular the evidence is scarce for at low levels that are below the current international guidelines. Methods: We construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Specifically, future extensions of ZAPPA can add emerging knowledge on new adverse health impacts of exposure to PM 2.5 and incorporate treatment for additional pollutants, such as NO 2 from combustion sources, which are also known to cause adverse human health impacts. 67 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, future extensions of ZAPPA can add emerging knowledge on new adverse health impacts of exposure to PM 2.5 and incorporate treatment for additional pollutants, such as NO 2 from combustion sources, which are also known to cause adverse human health impacts. 67 …”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that ZAPPA can be expanded to other cities in the U.S. and the world for assessing PM 2.5 -based health impacts, designing emissions reduction scenarios, and to further identify vulnerable populations with disproportionate exposures to air pollution sources. Specifically, future extensions of ZAPPA can add emerging knowledge on new adverse health impacts of exposure to PM 2.5 and incorporate treatment for additional pollutants, such as NO 2 from combustion sources, which are also known to cause adverse human health impacts …”
Section: Discussionmentioning
confidence: 99%
“…In these investigations, a linear exposure–response was detected starting from a very low exposure level as in the Quin et al. ( 2021 ) study. It is important to note that all the studies together span at least three decades and took place in multiple cities and continents; consequently, combustion-related air pollution mixtures were quite different between study populations.…”
mentioning
confidence: 92%
“…The study by Qian et al. 2 that Forastiere and Peters examined appeared in the same issue of Environmental Health Perspectives as their perspective. As Forastiere and Peters noted, 1 this retrospective registry-based study in the southeastern United States showed a direct link between atmospheric nitrogen dioxide ( ) and mortality, and they noted also that had an independent effect after controlling for fine particulate matter (PM) and ozone.…”
mentioning
confidence: 99%
“…Qian et al. 2 also compared results from studies conducted in different countries, all of which showed various adverse effects of . Forastiere and Peters argued that because “combustion-related air pollution mixtures were quite different between study populations … even if other important copollutants of were not assessed … it is unlikely that the observed associations of and mortality are solely attributable to one of those copollutants.” 1 The implication seems to be that acts by itself and is not a marker for a more complex exposure.…”
mentioning
confidence: 99%